(untitled) (Palíndromo, 2016)
This article aims to scrutinize the anthological work, so far without trans- lation into Portuguese, Passions sans noms, from the semiotician Eric Lan- dowski, bringing its theoretical postu- lations in line with the cultural manifes- tations called Flash Mobs. We intend to outline the production of meanings of these happenings in the light of the inte- ractions schemes as restructured by the author throughout his theoretical pro- duction. In a contemporary conducive environment with new technologies that facilitated the emergence of Flash Mobs, these manifestations purposely sudden and ephemeral are amenable to analysis under semiotic assumptions that cover intersections between programmed and accidental interaction schemes.